2015
DOI: 10.1103/physrevb.92.045418
|View full text |Cite
|
Sign up to set email alerts
|

Design for a spin-Seebeck diode based on two-dimensional materials

Abstract: Studies of the Spin-Seebeck effect (SSE) are very important for the developments of fundamental science and novel low-power-consumption technologies. Spin-Seebeck diode (SSD), in which the spin current can be driven by a forward temperature gradient but not by a reverse temperature gradient, is a key unit in spin caloritronic devices. Here, we propose a new design of SSD using two-dimensional (2D) materials such as the silicene and phosphorene nanoribbons as the source and drain. Due to their unique band struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…This is a thermoelectric phenomenon and thereby the name of Seebeck diodes. Furthermore, the spin current can be also rectified as predicted in the spin Seebeck diodes [2][3][4][5][6]. Here, the spin current is generated via the experimentally demonstrated spin Seebeck effect [7][8][9].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is a thermoelectric phenomenon and thereby the name of Seebeck diodes. Furthermore, the spin current can be also rectified as predicted in the spin Seebeck diodes [2][3][4][5][6]. Here, the spin current is generated via the experimentally demonstrated spin Seebeck effect [7][8][9].…”
Section: Introductionmentioning
confidence: 88%
“…Now, the combination of superconductivity and spintronics can lead to novel functionalities with better performances [33,34]. In order to realize the spin Seebeck diode [2][3][4][5][6]. Either finite magnetic field D ¹ 0 Z or a nonzero polarization ¹ p 0 using the ferromagnet is necessary to break the spin symmetry of the transmission, viz.…”
Section: Formalismmentioning
confidence: 99%
“…On the other hand, due to its novel physics as well as its potential applications in environmental protection and energy conversion, spin caloritronics has attracted much recent interest [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Besides the spin Seebeck effect using magnons as carries, the spin-dependent Seebeck effect (SSE) using fermions as carries has also attracted much recent attention in two dimensional graphenelike materials, such as graphene [30][31][32] and silicene [33][34][35][36][37][38][39]. In these works thermally induced spin-polarized current [30,31], thermoelectric spin voltage [32], and spin-Seebeck diode [33] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the spin Seebeck effect using magnons as carries, the spin-dependent Seebeck effect (SSE) using fermions as carries has also attracted much recent attention in two dimensional graphenelike materials, such as graphene [30][31][32] and silicene [33][34][35][36][37][38][39]. In these works thermally induced spin-polarized current [30,31], thermoelectric spin voltage [32], and spin-Seebeck diode [33] have been reported. Due to the presence of the valley degree of the freedom, similar to SSE, valley Seebeck effect is also put forward, where the pure or valley polarized current can be induced by the temperature gradient [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies showed that spin-Seebeck rectification and negative differential SSE can exist in junctions of a metal and magnetic insulator (MI) if the electronic density of states (DOS) in the metal lead strongly fluctuates [11]. Moreover, the spin-Seebeck diode effect was proposed in either a spin valve nanopillar made of two permalloy circular disks [12], or in a two-dimensional junction of functionalized materials [13]; both can produce unidirectional spin-Seebeck currents for spintronic applications.…”
Section: Introductionmentioning
confidence: 99%